2010
DOI: 10.1038/ajg.2009.712
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Multicenter Trial Comparing Push-and-Pull Enteroscopy With the Single- and Double-Balloon Techniques in Patients With Small-Bowel Disorders

Abstract: The complete enteroscopy rate was three times higher with DBE than with SBE, accompanied by a higher diagnostic yield. DBE must therefore continue to be regarded as the nonsurgical gold standard procedure for deep small-bowel endoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
163
5
10

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(189 citation statements)
references
References 29 publications
11
163
5
10
Order By: Relevance
“…In total 44 patients underwent antegrade DBE, 11 retrograde DBE and 34 underwent both. Sixteen of the 34 had complete enteroscopy [5,6] . In patients with obscure gastrointestinal bleeding (OGIB) and negative VCE exams, DBE was guided by the patient's history.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total 44 patients underwent antegrade DBE, 11 retrograde DBE and 34 underwent both. Sixteen of the 34 had complete enteroscopy [5,6] . In patients with obscure gastrointestinal bleeding (OGIB) and negative VCE exams, DBE was guided by the patient's history.…”
Section: Patientsmentioning
confidence: 99%
“…Although total enteroscopy can be accomplished, it typically requires antegrade and retrograde approaches. The rate of total enteroscopy varies between 11%-66% [5,6] . In most clinical situations, VCE is performed initially [3] .…”
Section: Introductionmentioning
confidence: 99%
“…Although less data have been published regarding SBE outcomes compared with DBE, initial studies reported somewhat lower diagnostic yields, potentially due to decreased rates of total enteroscopy [4,5]. Higher total enteroscopy rates and therapeutic interventions with DBE compared to SBE were reported when the enteroscope balloon was removed from the Fujinon system [6]. Nevertheless, a subsequent randomized controlled trial did not confirm these results [7].…”
mentioning
confidence: 58%
“…Rate of complete small bowel investigations seems to be more regularly achievable using doubleballoon rather than the single-balloon technique whereas the therapeutic impact was similar with SBE and DBE [6][7][8]. Complications are reported in less than 5% of procedures and include pancreatitis (< 1%), bleeding, and perforation, with the rate of complications increasing in therapeutic interventions [9].…”
Section: Endoscopic Imaging In Small Bowel Crohn's Diseasementioning
confidence: 99%